At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Step-by-step explanation:
Given : x³ - 3x + 1 = 0 has roots α , β and γ
To Find : Cubic equation with roots α² , β² and γ²
Solution:
x³ - 3x + 1 = 0 has roots α , β and γ
α + β + γ = 0 as no coefficient of x²
αβ + βγ + αγ = - 3
αβγ = - 1
α² + β² + γ² = (α + β + γ )² - 2(αβ + βγ + αγ)
= 0 - 2(-3)
= 6
α² β² + β² γ² + α² γ² = ?
αβ + βγ + αγ = - 3
Squaring both sides
=>α² β² + β² γ² + α² γ² + 2αβγ( α + β + γ ) = 9
=> α² β² + β² γ² + α² γ² + 0 = 0
=> α² β² + β² γ² + α² γ² = 9
α² β² γ² = (αβγ )² = 1
α² + β² + γ² = 6
α² β² + β² γ² + α² γ² = 9
α² β² γ² = 1
x³ - 6x² + 9x - 1 = 0
x³ - 6x² +9x - 1 = 0 is the required equation
its given α , β , γ are roots and α² , β² , γ² are roots of new
so just replace x with √x in x³ - 3x + 1 = 0
=> (√x)³ - 3√x + 1 = 0
=> x√x - 3√x = - 1
=> √x(x - 3) = - 1
Squaring both sides
=> x(x - 3)² = 1
=> x( x² - 6x + 9) = 1
=> x³ - 6x² + 9x - 1 = 0
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.